Kekerasan Seksual di Lingkungan Pendidikan dan Pencegahannya - Sopyandi Sopyandi; Sujarwo Sujarwo (FKIP, Universitas Palangka Raya, 2023)
Cases of sexual violence in Indonesia in the near future are always increasing from year to year, and victims are not only adults but also children, including in religious circles (pesantren). The phenomenon of sexual violence against children is becoming more and more common and has become a special concern in the world of education. The increase in cases of sexual violence is seen in the quantity or number of cases that occur. And to make matters worse, the perpetrators come from an educational environment such as a boarding school which is an Islamic educational institution. The method used in this research is the case study method. The focus of this article is sexual violence in pesantren and its prevention. With efforts to provide sex education, the mindset of providing sex education to students from an early age is important and not taboo